Impact of the invasive tree black locust on soil properties of Mediterranean stone pine-holm oak forests - De Marco, Anna; Arena, Carmen; Giordano, Maria; De Santo, Amalia Virzo (PLANT AND SOIL, 2013)
Invasion by N-2-fixing species may alter biogeochemical processes. We hypothesized that the grade of invasion by the N-2-fixer black locust (Robinia pseudoacacia L.) could be related to the distribution and pools of carbon (C) and nitrogen (N) along the profile of two Mediterranean mixed forests of stone pine (Pinus pinea L.) and holm oak (Quercus ilex L.). A low-invaded (LIN) and a high-invaded (HIN) mixed forest were studied. We assessed: N concentration in green and in senescent leaves; C and N pools along the soil profile; seasonal changes of soluble C and N fractions, and microbial activity. Compared to coexisting holm oak and stone pine, black locust had higher N content in green and in senescent leaves. In the mineral soil: N stocks were similar in LIN and HIN; water soluble C and microbial activity, were lower in HIN compared to LIN; water soluble N showed seasonal changes consistent with tree growth activity in both HIN and LIN. In the organic layer of HIN, C and N stocks were about twofold larger than expected on the basis of stand density. Black locust increased C and N stocks in the upper organic layers that are more vulnerable to disturbance. However, it did not increase N stocks in the mineral soil.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: C and N stocks; Exotic N-2-fixing tree; litter; organic layer and mineral soil; Water soluble C and N

Ranges of nutrient concentrations in Quercus ilex leaves at natural and urban sites - Maisto, Giulia; Baldantoni, Daniela; De Marco, Anna; Alfani, Anna; De Santo, Amalia Virzo (JOURNAL OF PLANT NUTRITION AND SOIL SCIENCE, 2013)
The leaf nutrient concentrations and the N-to-nutrient ratios were analyzed to evaluate the nutritional status of holm oaks (Quercus ilex L.) experiencing various anthropogenic pressures. Leaves (1 year old) of Q. ilex and surface soil (0-5cm) surrounding the trees were collected at seven natural and seven urban sites in Campania Region (Southern Italy) and analyzed for the concentrations of macro (C, N, P, S) and micronutrients (Mn, K, Na, Cu, Mg, Ca, Fe, Zn). The available soil fraction of micronutrients was also evaluated. The nutrients showed different concentration ranges for the natural and the urban sites in the soil (total and available) and in the leaves, that we reported separately. Organic-matter content and macronutrient concentrations were higher in the natural soils, while the highest leaf N, S, and P concentrations were found at some urban sites. Concentrations of Cu, Na and Zn both in leaves and soil, and Mg and Fe in leaves from the urban sites appeared to be affected by air depositions. Manganese was the only micronutrient to show higher concentrations at the natural than at the urban sites, both in soil and leaves. For this nutrient, in addition, a relationship between leaf and available soil concentrations was found at the natural sites. The ratios between the concentrations of N and each studied nutrient in the leaves highlighted a different nutritional status between the plants from the natural and urban sites.
Keywords: Campania Region; Holm oak; leaf N-to-nutrient ratios; southern italy; total and available soil nutrient concentrations

Litter decomposition in Mediterranean ecosystems: Modelling the controlling role of climatic conditions and litter quality - Incerti, Guido; Bonanomi, Giuliano; Giannino, Francesco; Rutigliano, Flora Angela; Piermatteo, Daniela; Castaldi, Simona; De Marco, Anna; Fierro, Angelo; Fioretto, Antonietta; Maggi, Oriana; Papa, Stefania; Persiani, Anna Maria; et al. (Applied Soil Ecology, 2011)
A new process-based model of litter decomposition, characterized by detailed climatic data input and simple litter quality parameters, is proposed. Compared to existing litter carbon models, speciﬁc implementations for temperature and moisture limiting effects have been adopted. The model is capable to represent decomposition processes in Mediterranean ecosystems, with summer drought slowing down, even at optimal temperatures, the litter decay rates of sclerophyll plants whose leaf masses are rich in structural compounds and low in N content. The model was calibrated by a best ﬁtting procedure of two different datasets. First, unpublished results of litterbag experiments on leaf litter of 9 Mediterranean species, decomposing under controlled and not limiting temperature and water conditions, have been used to estimate the decay rate dependency from litter quality that was deﬁned by only three initial C pools (labile, stable and recalcitrant compounds) instead of traditional N-based indices. Second, a set of published data from three medium-term ﬁeld experiments on a single species, Phillyrea angustifolia, decomposing under different climatic conditions, have been used to estimate the limiting effects of temperature and moisture. The model was then validated against published data on seven other species and showed a correct reproduction ofthemajor patterns of littermass loss during decomposition processes of other seven different Mediterranean species. The model simulations, satisfactory for different litter types under a wide range of climatic conditions, suggest that factors which were not taken into account, such as initial litter N contents, microclimatic variations related to stand structure, soil chemistry and texture, and microbial communities, are not very signiﬁcant for assessing decomposition dynamics in Mediterranean ecosystems. The minimal requirements of input data, the simple structure, and the easiness of parameterisation make our model, among the many other available litter carbon models, an attractive alternative for different research purposes, at least for Mediterranean ecosystems.
Keywords: C model; C/N ratio; Initial C pools; process-based model; Semi-arid ecosystems; System dynamics

Nutrient dynamics in litter mixtures of four Mediterranean maquis species decomposing in situ - Maisto, Giulia; De Marco, Anna; Meola, Angela; Sessa, Ludovica; Virzo De Santo, Amalia (Soil Biology and Biochemistry, 2011)
In natural conditions, litters shed from different species become mixed with each other, and decompose together. Most studies deal with decomposition of individual species; few studies investigate the inﬂuence of litter mixing on decomposition and nutrient dynamics; the results are contradictory as positive, negative, or no effect, of litter mixing have been observed. In this study we test the hypothesis: i) that litter mixing in the Mediterranean maquis, a nutrient poor, high diversity ecosystem, produces non-additive effects on nutrient dynamics; ii) that the effects vary with the composition in species of the mixture and with the relative amount of the species component the mixture. Two types of 3-species mixtures were set up; one contained three sclerophylls, Phillyrea angustifolia, Pistacia lentiscus and Quercus ilex; the other contained the ﬁrst two species with the mesophyll Cistus. Litterbags, containing monospeciﬁc litters and even and uneven mixtures, were incubated under natural condition in situ; even mixtures had the 3 species in equal proportion, whereas uneven mixtures had one of the species as dominant (50%) and the other two species in equal proportion (25%:25%). Litterbags were retrieved after 92, 188 and 403 days; litters from the mixtures were separately analyzed for mass loss and content of nitrogen (N), potassium (K), sodium (Na), calcium (Ca), magnesium (Mg), manganese (Mn), iron (Fe), copper (Cu), and zinc (Zn). Results indicate that mixing inﬂuences the dynamics of N, Mn, Ca, Mg, Fe, Cu and Zn, but scarcely affects the dynamics of K and Na. The comparison of observed to expected values for changes of nutrients in litterbags indicates the occurrence of non-additive effects of litter mixing on movements of N, Fe, Cu, and Zn to or from the litterbags containing the mixtures. The effects depend on the composition in species of the mixture, whereas the relative amount of the species component the mixture is not relevant.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Interactions among litters; Lignin; litter decomposition; Manganese; Non-additive effects of litter mixing